Strategies And Methods of Teaching And Learning Information Technology Terminology - Abdirazzakova Sadoqat Alimbayevna (Zien Journals, 2021)
The unprecedented growth of technology and development has made it necessary for contemporary society and its non-expert members to keep up and make use of it. The following article looks into the methods of teaching terminology related to IT
Keywords: Pedagogical One on Principle; Science Development; Pervades the Media and The Internet